Analisis Penulisan Latar Belakang Penelitian mengacu Prototipe dengan Penerapan HOTS-Interrogation - Zahrotun Nisa; Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to analyze the difficulties of master's level students in writing scientific articles, especially writing research backgrounds. This study uses a qualitative approach by applying the HOTS-interrogation method. The results and discussion of this study indicate that the background prototype is needed by the participants as a reference for writing research background, so that through the application of HOTS analysis, evaluation, and creation of research background writing can be carried out according to the prototype reference, and the interrogation method is then used to prove the ability of 21 participants. respondents in writing research background. This study concluded that the participants proved able to overcome difficulties in making research backgrounds through prototype reference through the application of HOTS-interrogation.